Access to language and cognitive development - Siegal, Michael; Surian, Luca. (Oxford : Oxford University Press, 2012)
To what extent, and in what ways, is a child's cognitive development influenced by their early experience of, and access to, language? What are the affects on development of impaired access to language? This book considers how possessing an enhanced or impaired access to language influences a child's development.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references.
Keywords: Cognition in children; Language acquisition